Characterization of nano-scale oxides in austenitic stainless steel processed by powder bed fusion. (October 2018) - Yan, Fuyao; Xiong, Wei; Faierson, Eric; Olson, Gregory B.
Abstract: Nano-scale MnSiO3 Rhodonite particles were observed in 316L stainless steel fabricated by selective laser melting (SLM). These oxide particles act as Zener-pinning particles providing dragging force to retard grain growth, and enhance strength through the comparison of Hall-Petch effects between SLM 316L and commercial wrought 316L under 1200 °C isothermal heat treatment. The metastable Rhodonite particles were observed to in-situ convert to stable MnCr2 O4 Spinel particles at 1200 °C, as predicted by computational thermodynamics. This work introduces nano-scale oxides, which are normally detrimental inclusions, as a new type of particle for grain refinement and strengthening through their refinement in additive manufacturing. Graphical abstract: Unlabelled Image